2012
DOI: 10.1039/c2cc16156g
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic biofuel cells utilizing a biomimetic cofactor

Abstract: The performance of immobilized enzyme systems is often limited by cofactor diffusion and regeneration. Here, we demonstrate an engineered enzyme capable of utilizing the minimal cofactor nicotinamide mononucleotide (NMN(+)) to address these limitations. Significant gains in performance are observed with NMN(+) in immobilized systems, despite a decreased turnover rate with the minimal cofactor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 20 publications
2
58
0
Order By: Relevance
“…With respect to the second goal, the use of more stable thermoenzymes, better mediators and cofactors, and better formulation of enzymes can prolong the lifetime of EFCs to months or longer at room temperature, similar to the proteases used in liquid detergents. Moreover, costly and labile NAD can be replaced with low-cost and stable biomimics 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the second goal, the use of more stable thermoenzymes, better mediators and cofactors, and better formulation of enzymes can prolong the lifetime of EFCs to months or longer at room temperature, similar to the proteases used in liquid detergents. Moreover, costly and labile NAD can be replaced with low-cost and stable biomimics 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…A mutant with changes in three amino acids can work on NMN [135]. Recently, Scott et al demonstrated that engineered Pyrococcus furiosus alcohol dehydrogenase has an ability to work with NMN [59]. By following the same strategy, our lab has modified a thermophilic G6PDH that can work with NMN although its activity is very low (data not published).…”
Section: Redox Enzyme Engineeringmentioning
confidence: 86%
“…For example, both enzymatic pathways for hydrogen generation from polysaccharides and alcohol production from glucose do not need ATP for sugar phosphorylation, completely different from pathways occurring in microbes [20,24]. Another solution is the use of the low-cost biomimetic cofactors that have similar functions with natural cofactors [59][60][61]. Redox enzyme engineering has achieved the change of cofactor preference from one to another.…”
Section: Cell-free Biosystems For Biomanufacturing: Problems and Theimentioning
confidence: 97%
See 1 more Smart Citation
“…In 2010, Campbell et al used rational design to change the specificity of an ADH to have a higher affinity for nicotinamide mononucleotide (NMNH) rather than NADH, broadening the specificity for the cofactor [40]. By engineering the active site of an NADH-dependent ADH from Pyrococcus furiosus, Campbell et al were able to substitute NMN in place of NAD and improve BFC performance [41]. Although the OCP dropped from 0.642 to 0.593 V, the current density increased from 16.1 to 22.8 μA cm 2 , suggesting increased mass transfer for the minimal cofactor.…”
Section: Protein Engineeringmentioning
confidence: 99%